THE INFLUENCE OF TEACHING FACTORY LEARNING MODEL IMPLEMENTATION TO THE STUDENTS’ OCCUPATIONAL READINESS - Ahmad Mustamil Khoiron (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study examines the significance level of teaching factory learning model to the occupational readiness of the students. Using the research design of a quantitative approach with causal comparative, the study included the following variables: teaching factory learning model (X) and occupational readiness (Y).The population consisted of 30 students of the study program of Automotive Engineering Education, Faculty of Engineering, State University of Semarang. They were selected using proportional random sampling technique. The data was analysed using descriptive and inferential statistical analysis. The findings shows the implemetation of teaching factory learning models (X) contributes significantly with the percentage of 22.80% to the occupational-readiness (Y). These results suggest that the implementation of teaching factory in the learning process is strongly recommended for the vocational educators both lecturers and teachers. The implementation can be adjusted to suit the conditions and the learning resources available in the educational institution.